Evolution of human from primates - A review on religio-scientific discourse - Zayan, Mohamed Jalal; John, Akbar; Hashi, Abdurezak Abdulahi; Chowdhury, Ahmed Jalal Khan (Malaysian Nature Society, 2017)
The term evolution is the self-modification by any organism to adapt to the changes to their living environment. For many decades, arguments were put forth by scientists to refute the religious beliefs on divinely creation of creatures especially humans. Though, to some extent, the process of evolution is true due to interbreeding efficiency of living organisms, the single ancestral lineage from unicellular to complex multicellular organisms is still under debate among the researchers and also between scientists and theologists. Many arguments were placed by both the groups to prove/refute the existence and continuous process of evolution. However, concrete scientific evidence to prove the evolution of human from primates (immediate ancestral lineage) is still questionable. Numerous scientific articles and books attempted to address this issue put forth by scientific and religious communities. However, they failed to address the connection and turning point in arguments between scientific and religious communities. Hence, the present paper was aimed to review the view point of both pro-evolutionists and arguments given by the religio-scientific community to answer the misconception on primate-human evolution. It also addresses the purpose of human creation in line with the arguments from philosophers and theologist.